Defining the sovereign community : the Czech and Slovak Republics - Nedelsky, Nadya (Democracy, citizenship, and constitutionalism., 2009)
Defining the Sovereign Community asks why the two nations have defined sovereignty so differently and what impact these choices have had on individual and minority rights and participation.